Redundant IEC 61850 communication protocols in substation automation - Taikina-aho, Markku (My University, 2011)
The standard IEC 61850 has been adopted with open arms by the power system automation market. The first version of the standard published in 2005 did not however pay any attention to redundant communication aspects of the substation automation network. The recent extensions to the standard however corrected this defect and bring redundancy into view, adopting two high availability redundancy protocols from the existing standard IEC 62439-3: Parallel Redundancy Protocol (PRP) and High-availability Seamless Redundancy (HSR). These two protocols provide seamless (0 s.) network recovery times and fulfill even the most demanding requirements for substation automation network. In this thesis, these two redundancy protocols, their usage and possibilities in substation automation are investigated. At first, the IEC 61850 features, substation communication network topologies, and also the redundancy protocols and methods used today are presented. After this, the protocols PRP and HSR are discussed more deeply. The theoretical part is followed by a test of a system with PRP and ABB devices to give general notes and clarify possible problems when building such a system, and to investigate if the ABB PRP implementation is accordant with the standard IEC 62439-3. The objective of this thesis was to bring information and early experience about the two high-availability redundancy protocols, as they will be gradually introduced in the projects of the target company. The test confirmed that the current PRP version is ready to be used with the few ABB substation automation products that support it at the moment. However, a new version of PRP has been introduced and it will gradually replace the present version, bringing compatibility with HSR networks. HSR is not yet found on the market, but is expected to come to use in the very near future.
Keywords: Substation automation; IEC 61850; IEC 62439; communication; redundancy; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|